2007
DOI: 10.1080/16506070701374256
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Cognitive Content between Depressed and Anxious Outpatients

Abstract: Quantitative research suggests that depressed and anxious patients can be differentiated based on their cognitive content. This study used qualitative research methods to separate the specific components of open-ended depressive and anxious thought content in 79 psychiatric outpatients. Patients with major depressive disorder (MDD; n = 36), generalized anxiety disorder (GAD; n = 10), and other psychiatric disorders (PC; n = 33) were instructed to (a) describe their most bothersome problem; (b) imagine the wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Differences can be explained by the use of different cognitive constructs (for example the Cognitions Checklist that was not included in NESDA), different sample sizes, and the fact that investigations did not always take place in clinical settings. Other research, however, demonstrated that MDD and GAD indeed have disorder-specific cognitive profiles [11]. Despite the commonalities in cognitive profiles in MDD and GAD, we also found differences that seem to be characteristic for the disorders.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Differences can be explained by the use of different cognitive constructs (for example the Cognitions Checklist that was not included in NESDA), different sample sizes, and the fact that investigations did not always take place in clinical settings. Other research, however, demonstrated that MDD and GAD indeed have disorder-specific cognitive profiles [11]. Despite the commonalities in cognitive profiles in MDD and GAD, we also found differences that seem to be characteristic for the disorders.…”
Section: Discussioncontrasting
confidence: 49%
“…The general component refers to a factor that anxiety and depressive disorders have in common, the specific component is shared with certain disorders but not all, and the unique component is a characteristic of a particular disorder differentiating it from all the others. Many studies have investigated aspects of the cognitive content-specificity model and the tripartite model [11,20-24]. Previous research showed that the constructs of the cognitive content-specificity model and the tripartite model are meaningfully correlated, and that the integration of the models may better discriminate between anxiety (high negative affect and anxiety cognitions) and depression (high negative affect, low positive affect, and depression cognitions) than either model alone [25-27].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive accounts of anxiety dysfunction attribute both heightened anxiety vulnerability and clinical anxiety to maladaptive patterns of selective information processing. They have been motivated by the observation that patients with anxiety disorders commonly report experiencing distinctly threatening thoughts of a type that plausibly could elicit, sustain, or intensify their anxiety symptoms (e.g., Ghahramanlou-Holloway et al 2007). However, theoretical models developed to explain these idiosyncrasies in thought content causally attributed them to systematic biases in low-level cognitive mechanisms not readily available to introspective assessment.…”
Section: Background To Cognitive Bias Modification Research Cognitivementioning
confidence: 99%
“…Additionally, as several studies demonstrating a relationship between catastrophizing and depression have not controlled for anxiety (e.g., Abela 2001;Ghahramanlou-Holloway et al 2007;Hankin and Abramson 2002), this study assessed and controlled for anxiety in an effort to distinguish the contribution of catastrophizing to anxiety from that to depression. Although a relationship between catastrophizing and depression independent of anxiety has been observed across a sample of children and adolescents diagnosed with anxiety (Weems et al 2001), the present study will examine this relationship in a sample of youth without clinical levels of anxiety in order to ascertain the specific contribution of catastrophizing to depressive symptoms outside of the context of elevated anxiety.…”
Section: Catastrophizing Depression and Anxiety In Childrenmentioning
confidence: 99%